Projeto e implementação de um acionamento elétrico embarcado para auxílio à tração humana em sistemas de transporte de carga - Leonardo Adolpho Rodrigues da Silva (2014)
The current PhD thesis presents a complete methodology applied to project and construction of a solution applied to aid people who need to move loads in professional or daily activities. This solution joins the capacity of electrical drives to produce mechanical force with the human brain's capacity to choose the trajectory references demanded by the drive. Since the electrical drive is embedded into a vehicle, the last is qualied as a robot and, in this approach, the present solution is qualied as a human-robot cooperation system. To project and build this system, it were evaluated the muscle-skeleton diseases committed by people who work with load displacements executed by humans, as it were evaluated the scientic jobs which describe the state-of-art in the human-robot cooperation technology. From the last evaluation, it was observed that the cooperation systems have a very expensive constructive structure, a net load capacity very low or even they are not developed taking into account project options to aid in the comfort perception by the person who interacts with the vehicle. Such contribution opportunities were so explored through a detailed project, which resulted in the rating of power elements capable to develop in the most ecient and economic way the monitored activities done by a specic professional group taken as an example scenario for the methodology. It's highlighted that this methodology presents an innovative approach to determine the load torque, which rejects the necessity to measure the inclination from the surface where the vehicle is moving. To ensure a safety operation to Vecarr, it was researched the force dynamic commands imposed by the human intention to move the vehicle, as the dynamics of the legs movement. From these studies, it were synthesized controllers that enable dierent operational modes to the load transportation solution, being those modes related to the following boundary conditions: the touch comfort sensed by the person that cooperates with the vehicle or the possibility to develop higher nal speeds. Any of those options is readily attachable to the vehicle, demanding just software modications or load cell removal/installation. In any of those operational modes, there are guaranteed the following characteristics: the vehicle is moved by the human intention, dispensing any specic training; the vehicle is kept stopped in inclined surfaces, even when the user embed or remove loads from its chart; the user choose dynamically the vehicle's displacement speed.